2019
DOI: 10.17306/j.afs.0672
|View full text |Cite
|
Sign up to set email alerts
|

The quality of cold-pressed rapeseed oil obtained from seeds of Brassica napus L. with increased moisture content

Abstract: Background. The basic parameter influencing the quality of cold-pressed oil is the quality of seeds used for pressing. Adverse moisture content and storage temperature of rape seeds may affect the quality of oil obtained from them. This paper presents the effects of increased rapeseed moisture content on the quality of the oil pressed. Material and methods. The material used for the tests was rapeseed (canola) cv. PR 46 W14. The moisture content of the seeds was adjusted to 10%, 12% and 20%, and the seeds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
5
7
0
Order By: Relevance
“…[ 13 c] This is because the high moisture content of the seeds, in holding time before pressing, as well as during extraction, intensifies enzymatic activity (especially lipoxygenase) and increases oxidative reactions, resulting in increased levels of oil hydroperoxides. These results concur with the previous findings by Rokosik et al., [ 7 ] Akinoso et al., [ 14 ] and Mazaheri et al. [ 11 ] Akinoso et al.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…[ 13 c] This is because the high moisture content of the seeds, in holding time before pressing, as well as during extraction, intensifies enzymatic activity (especially lipoxygenase) and increases oxidative reactions, resulting in increased levels of oil hydroperoxides. These results concur with the previous findings by Rokosik et al., [ 7 ] Akinoso et al., [ 14 ] and Mazaheri et al. [ 11 ] Akinoso et al.…”
Section: Resultssupporting
confidence: 94%
“…[13c] This is because the high moisture content of the seeds, in holding time before pressing, as well as during extraction, intensifies enzymatic activity (especially lipoxygenase) and increases oxidative reactions, resulting in increased levels of oil hydroperoxides. These results concur with the previous findings by Rokosik et al, [7] Akinoso et al, [14] and Mazaheri et al [11] Akinoso et al [14] reported that increasing the moisture content of un-refined sesame oil from 4% to 16% increased the PV from 3.9 to 15.4 (mEq O 2 /kg oil). Also, another study showed that increasing the moisture content from 5.1% to 8.0% increased the PV in black cumin seed from 5.6 ± 0.5 to 7.8 ± 0.2 (mEq O 2 /kg oil).…”
Section: Peroxide Valuesupporting
confidence: 92%
See 3 more Smart Citations